2015
DOI: 10.1021/acs.nanolett.5b02985
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Size Effect in Organometal Halide Perovskite Nanoplatelets

Abstract: Organometal halide perovskites have recently emerged displaying a huge potential for not only photovoltaic, but also light emitting applications. Exploiting the optical properties of specifically tailored perovskite nanocrystals could greatly enhance the efficiency and functionality of applications based on this material. In this study, we investigate the quantum size effect in colloidal organometal halide perovskite nanoplatelets. By tuning the ratio of the organic cations used, we can control the thickness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

59
981
5
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 839 publications
(1,068 citation statements)
references
References 48 publications
59
981
5
4
Order By: Relevance
“…By systematically varying the ratio of the organic cations used (octylammonium and MA). Sichert et al 25 showed how the perovskite NCs gradually decrease in thickness from large cubic crystals to ultrathin nanoplatelets down to a thickness of only a single perovskite unit cell. The octylammonium molecule is too large to fit into the perovskite crystal structure and so leads to termination of the crystal growth on binding to the perovskite, however predominantly in one direction.…”
Section: Synthesis Of Perovskite Ncsmentioning
confidence: 99%
See 4 more Smart Citations
“…By systematically varying the ratio of the organic cations used (octylammonium and MA). Sichert et al 25 showed how the perovskite NCs gradually decrease in thickness from large cubic crystals to ultrathin nanoplatelets down to a thickness of only a single perovskite unit cell. The octylammonium molecule is too large to fit into the perovskite crystal structure and so leads to termination of the crystal growth on binding to the perovskite, however predominantly in one direction.…”
Section: Synthesis Of Perovskite Ncsmentioning
confidence: 99%
“…The authors reasoned that the increased PLQY of the NCs with respect to micrometer-sized bulk perovskite particles resulted from higher excitonic binding energies of up to nearly 400 meV, when the size of the NCs approached the Bohr radius of the respective perovskite, on the order of 13-30 Å, depending on the material. 25,47,48 By replacing the bromide anion with chloride or iodide, or by using mixtures of the three anions, the authors were able to obtain perovskite NC dispersions emitting throughout the full range of the visible spectrum (Figure 3c). The average PL lifetimes of these NCs were considerably shorter than for the respective bulk films.…”
Section: Synthesis Of Perovskite Ncsmentioning
confidence: 99%
See 3 more Smart Citations